Short Term Neurocognitive and Behavioral Outcome of Acute CNS Infection in Children in a Tertiary Neurology Hospital - Rashid, Muhammed Anisur; Hussain, Sharmin; Happy, Romana Akter; Moniruzzaman, Morshed Md; Eman Rashed, Abu Jafar Muhammad Kamrul; Debnath, Bithi; Shahed, Md Humayun; Saha, Narayan Chandra (Journal of Rangpur Medical College, 2026)
Background: Acute central nervous system (CNS) infections remain a major cause of childhood morbidity and mortality worldwide. Although neurocognitive and behavioral sequelae are well recognized, data from Bangladesh are limited. Objective: This study evaluated short-term neurocognitive and behavioral outcomes among children hospitalized with acute CNS infections. Methods: A prospective cohort study was conducted in the Paediatric Neurology Department at the National Institute of Neuroscience and Hospital from July 2021 to June 2022 on 120 children with acute CNS infections. Demographic data, clinical features, neurological status, and neurocognitive and behavioral performance were assessed at discharge, 1–2 weeks, and 3 months post-discharge using structured questionnaires. Data were analyzed with SPSS 24. Results: The mean age was 6.3±4.3 years, with male predominance (71.7%); most children were from rural areas. Nearly half presented within one week of symptom onset, commonly with seizures (60.8%), fever (55%), Kering’s sign (50.8%), and neck rigidity (41.6%). Encephalitis (50%) and meningitis (42.5%) were the predominant diagnoses, with Streptococcus pneumoniae and Neisseria meningitidis frequently identified. More than half had stage-II disease on admission. Moderate clinical outcomes were observed in 56.6% at discharge. Motor deficits were common in encephalitis, while seizures predominated in meningitis. Disease severity was strongly associated with final clinical outcome (p<0.001), and hospital stay varied significantly by infection type (p<0.001). Neurocognitive and behavioral scores were mostly impaired at baseline but improved across follow-ups. Disease severity did not significantly influence cognitive trajectories. Behavioral outcomes at discharge differed by disease stage (p=0.020) and were associated with clinical outcomes. Logistic regression showed no independent effect of meningitis, encephalitis, or hospital stay on cognitive or behavioral outcomes. Conclusion: Encephalitis and meningitis were the leading CNS infections, with most children experiencing moderate clinical improvement by discharge. Although disease severity predicted clinical outcomes, neither infection type nor hospital stay reliably predicted neurocognitive or behavioral recovery. Younger children showed poorer baseline functioning, but substantial improvement was observed over time. Clinical outcome at discharge emerged as the strongest correlation of short-term cognitive and behavioral progress. J Rang Med Col.2026 Mar;11(1): 78-84